2015
DOI: 10.1111/asj.12462
|View full text |Cite
|
Sign up to set email alerts
|

Correlated response of peripheral blood cytokines with selection for reduced mycoplasma pneumonia of swine lesions in Landrace pigs

Abstract: Mycoplasma pneumonia of swine (MPS) is responsible for significant economic losses in the swine industry. We selected Landrace pigs for reduced MPS pulmonary lesions over five generations, and measured concentrations of the following cytokines: interleukin (IL)-10, IL-13, IL-17, tumor necrosis factor (TNF)-α and interferon (IFN)-γ to estimate their correlation with MPS lesions. Sheep red blood cells (SRBC) were injected twice intramuscularly at 70 and 95 kg body weight. Blood serum samples were collected after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…increased environmental stress (Bossé et al, 2002). APP is rapidly eliminated by the innate immune response with little interference in the response to other pathogens (Sato et al, 2016), which may explain the positive r G between APP mean and MH found in our study. The r G estimate of MEAN with APP mean was positive and high at all time points, which may be because the serotypes of APP composed most of the Ab responses used to calculate MEAN, in addition to Ab responses to different APP serotypes showing high positive r G with each other.…”
Section: Genetic Parameterssupporting
confidence: 50%
See 1 more Smart Citation
“…increased environmental stress (Bossé et al, 2002). APP is rapidly eliminated by the innate immune response with little interference in the response to other pathogens (Sato et al, 2016), which may explain the positive r G between APP mean and MH found in our study. The r G estimate of MEAN with APP mean was positive and high at all time points, which may be because the serotypes of APP composed most of the Ab responses used to calculate MEAN, in addition to Ab responses to different APP serotypes showing high positive r G with each other.…”
Section: Genetic Parameterssupporting
confidence: 50%
“…Their results are similar to ours, where we obtained an average estimate of h 2 of 0.20 for the 50% seroconverted dataset. In another study, also analyzing the score of mycoplasma pneumonia of swine based on lung lesions in slaughtered pigs after vaccination at 6 and 8 weeks of age, the estimate of h 2 was 0.09 (Sato et al, 2016). These two results are not directly comparable with ours since the animals were experimentally infected and the phenotype analyzed was not the same.…”
Section: Genetic Parametersmentioning
confidence: 58%
“…In our previous study, the heritability of some immunity traits, such as MPS lesions, IL‐10, IL‐13, IL‐17, TNF‐α and IFN‐γ was also estimated low (Sato et al . ). Large environmental effects can be considered as a cause of low heritability estimates.…”
Section: Discussionmentioning
confidence: 97%
“…Sato et al . () reported the strong negative genetic correlation between MPS lesions and IL‐17 and found an increase in the breeding value for IL‐17 with selection in the MPS pulmonary lesion selected La line from the first to fifth generations. However, in this study, the La line did not show a significant increase in IL‐17.…”
Section: Discussionmentioning
confidence: 99%